Bridging Al-Dunya Wa Al-Diin: A Case Study on Prophetic-Integrative Education on Madrasah-Based Pesantren - Aziz, Hafidh (Faculty of Tarbiyah and Education, Universitas Islam Negeri (UIN) Sunan Kalijaga Yogyakarta, 2022)
Purpose – This study aims to analyze the practice of integrating education in Islamic boarding schools based on the perspective of prophetic education. Design/methods/approach – This study used a case study design and was conducted in Madrasah Tsanawiyah and Aliyah Modern Boarding School (PM) Al-Islam. Data were collected using interview observations and documentation and then analyzed using the Miles and Huberman interactive model. Findings – This study’s findings show that the spirit and practice of education in Madrasah Tsanawiyah and Aliyah Al-Islam align with prophetic values by prioritizing transcendent spirituality with critical humanist principles framed in the form of institutional integration and content. Research implications/limitations – This study strengthens and complements previous research findings on integrating Islamic scholarship in Islamic educational institutions in Indonesia. However, it is also important to continue conducting similar research with a broader scope to strengthen related research findings. Practical implications – The findings of this study can be a bridge to close the dichotomous gap and balance the gap in educational orientation to achieve educational goals between religious and pragmatic educational goals.